Between Testimony, Locus of Enunciation, and Critique: Absence/Presence of the Political in Chilean Philosophy Since 1973 [Entre Testimonio, Lugar de Enunciación y Crítica: Ausencia/Presencia de Lo Político en la Filosofía Chilena Desde 1973 - Friz-Echeverria, C (Universidad Nacional de Colombia, 2019)
The military dictatorship of Augusto Pinochet (1973-1990) created serious difficulties for philosophical work in Chile. Nevertheless, the suspension or absence of the political caused by the dictatorship, whose consequences can be observed until the present, sparked a special concern regarding the political in a group of Chilean philosophers. Their reflections evince a conscious and explicit acknowledgment of their locus of enunciation, which gives their work a marked testimonial and critical stance. 2017 © Universidad Nacional de Colombia.All Rights Reserved.